Association of Metabolic Syndrome Parameters with Kidney Stones in Indonesia (Unnes Journal of Public Health, 2019)
Kidney stone disease is common throughout the world. Elevated prevalence of kidney stones is often associated with metabolic syndrome itself. This study aimed to assess the association between kidney stones and metabolic syndrome parameters in differences gender. This was a cross-sectional study with Chi-square and multivariate logistic regression for data analysis from the secondary data Riskesdas 2013 with 26,063 respondents. Diagnosis of kidney stone based on Riskesdas 2013 interview, metabolic syndrome based on NCEP ATP-III and PERKENI. Result showed that there were 226 (0.9%) diagnosed kidney stones cases by doctors. After adjustment age, central obesity was dominant factor which associated with the risk of kidney stones in male (OR 1.9; 95% CI 1.3-2.9; p=0.003) and metabolic syndrome was dominant factor which associated with the risk of kidney stones in female (OR 6.1; 95% CI 3.4-11.3; p<0.001). The conclusion was that metabolic syndrome and central obesity were associated with risk of kidney stones.